Design Reviews in Immersive and Non-Immersive Collaborative Virtual Environments: Comparing Verbal Communication Structures. (May 2022) - Horvat, N.; Brnčić, M.; Perišić, M. M.; Martinec, T.; Bojčetić, N.; Škec, S.
Abstract: The paper explores the differences between immersive and non-immersive collaborative virtual environments (CVEs) during design reviews. Based on ten reviews with one designer and two reviewers, the study shows that CVEs affect verbal communication structure. More specifically, teams usually talked less, and reviewers exchanged significantly more turn sequences in immersive than in non-immersive CVEs. Regardless of the environment, most turn sequences were related to the designer, who usually talked the most. These findings contribute to the understanding of CVEs in virtual teams.